IMPLEMENTASI PROGRAM SUPERVISI PENDIDIKAN (Studi Kasus Pada Sekolah Dasar Distrik Merauke) - Wilhelmina Jeujanan; Yohanis Endes Teturan (SOCIETAS, 2014)
This study aims to determine the implementation of the policy program supervision of primary school education and the factors that affect implemntasi elementary school supervision programs.The research was conducted in Merauke District . The method used in this study is a qualitative analysis using the method wawacara depth, descriptive study was intended to describe the research data in accordance with the variables to be studied, without testing the hypothesis. in the data analysis model consists of three components: data reduction, data presentation, and conclusion.Based on the results obtained in this study is the implementation of the supervision program for supervisors in elementary school in Merauke district.The results show that have not been successful due to the absence of a clear work program received directly or indirectly to the school. So that all activities are carried out only lead to a mind of its own that is not through good planning. And this situation also affect the political situation .